Deep generative models: 4th MICCAI workshop, DGM4MICCAI 2024 : held in conjunction with MICCAI 2024, Marrakesh, Morocco, October 10, 2024 : proceedings - Mukhopadhyay, Anirban; Oksuz, Ilkay; Engelhardt, Sandy; Mehrof, Dorit; Yuan, Yixuan (Springer Nature Switzerland, 2025)
This book constitutes the proceedings of the 4th workshop on Deep Generative Models for Medical Image Computing and Computer Assisted Intervention, DGM4MICCAI 2024, held in conjunction with the 27th International conference on Medical Image Computing and Computer Assisted Intervention, MICCAI 2024, in Marrakesh, Morocco in October 2024. The 21 papers presented here were carefully reviewed and selected from 40 submissions. These papers deal with a broad range of topics, ranging from methodology (such as Causal inference, Latent interpretation, Generative factor analysis) to Applications (such as Mammography, Vessel imaging, Surgical videos and more).
Keywords: Konferenzschrift